Experimental and Theoretical Investigations on the Use of Pumpkin Peel as a Sustainable Biomass Anticorrosion Agent for Aluminum in HCl Solutions - Reem D. Alghamdi; Laila S. Alqarni; Maha D. Alghamdi; N. F. Alotaibi; Hend Gadow (Journal of Chemistry)
The sustainable plant-derived biomass are now understood to be important sources for the prevention of corrosion in metallic alloys. This study examined the effect of a potential novel low-cost, low-toxicity inhibitor utilizing pumpkin peel extract (PPE) on aluminum corrosion hydrochloric acid 1M HCl medium. Several experimental methods were used to investigate the inhibitor effect of PPE which include, AFM-XPS surface analysis, electrochemical studies (electrochemical impedance spectroscopy-electrochemical frequency modulation-potentiodynamics), and weight loss procedures. According to the weight loss results, when PPE is introduced to a 1M HCl solution, the inhibitory performance rises up to 95.42% with an increase in PPE concentration in the range of 0–300 ppm at 25°C. Potentiodynamic results showed the investigated PPE inhibitor is a mixed-type inhibitor. Corrosion inhibition at different temperatures was also examined, and the thermodynamic activation parameters were identified. It was found that the adsorption of the inhibitor on the aluminum followed the Langmuir and kinetic isotherm models. Quantum chemical indices contributed to a greater comprehension of the inhibitory mechanism. To investigate the configurational adsorption performance of the investigated PPE on the aluminum surface, molecular dynamics (MD) simulations were carried out.